The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1516-3180.2020.0021.r3.24062020
|View full text |Cite
|
Sign up to set email alerts
|

Can p63 serve as a biomarker for diagnosing giant cell tumor of bone? A systematic review and meta-analysis

Abstract: BACKGROUND: Tumor protein p63 (p63) has been reported to be highly expressed in giant cell tumor of bone (GCTB). Whether p63 can be treated as a diagnostic marker for GCTB remains unclear. OBJECTIVE: We conducted a meta-analysis to evaluate the applicability of p63 in diagnosing GCTB. DESIGN AND SETTING: Systematic review and meta-analysis carried out in a public hospital, Hong Kong, China. METHODS: We searched PubMed, EMBASE and the Cochrane Library from inception to April 30, 2019. Literature in English or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Both groups suggested using these biological markers for character assessment of bone neoplasms and to predict higher recurrence risks in PD-L1 expressing GCTB patients. Also, PD-L1 immune checkpoint inhibitors may be of clinical benefit for recurrent GCTB after denosumab [22 ▪▪ ].…”
Section: Diagnostics and Translational Researchmentioning
confidence: 99%
“…Both groups suggested using these biological markers for character assessment of bone neoplasms and to predict higher recurrence risks in PD-L1 expressing GCTB patients. Also, PD-L1 immune checkpoint inhibitors may be of clinical benefit for recurrent GCTB after denosumab [22 ▪▪ ].…”
Section: Diagnostics and Translational Researchmentioning
confidence: 99%
“…p63 has also been shown to be highly expressed in GCTB mononuclear neoplastic cells [65][66][67], but its usefulness is still to be determined. A meta-analysis of eight different studies including 335 GCTB patients showed that p63 is a helpful marker for GCTB diagnosis in critically ill patients, although it cannot be recommended as a single definitive diagnostic marker [68]. Finally, it has been suggested that high RANKL, IL-6, TNFα, SDF-1, and MCP-1 expression may help predict GCTB metastatic potential and prognosis, warranting further studies [69].…”
Section: Tumor Markersmentioning
confidence: 99%